(untitled) (Annals of Medical Research, 2021)
Aim: Bioceramic cements act as an alternative dentin replacement materials. The aim was to compare 24h push-out bond strength of novel OrthoMTA (BioMTA, Seoul, Korea) cement, and ProRootMTA(Dentsply Sirona, Tulsa, OK, USA) cement on root dentin.Materials and Methods: Twenty mandibular first premolar teeth were randomly divided into two groups. In each group, three 1-mm thick slices were obtained from the middle third of the root by cutting horizontally. Thirty root slices were obtained from ten roots. In the sectioned root slices, a cavity-like hole was prepared in the center and OrthoMTA and ProRootMTA were placed into the holes per groups. Samples were kept at 36°C, 100% humidity for 24h. The push-out bond strength was calculated (MPa). The critical point drying of all samples was performed followed by scanning electron microscopy evaluation. Results: Adhesive-type of failure at the cement-dentin interface, cohesive-type of failure within the bioceramic cement, and combination of adhesive- and cohesive-type of failures termed as mixed-type of failure were observed. One-way analysis of variance followed by Tukey’s test was performed (p0.05).Conclusion: Within the limitations of the in-vitro study the following conclusions can be drawn: 24h after hardening reaction, OrthoMTA presented superior bonding performance than that of ProRootMTA on root dentin (p0.05) and the most common type of failure was mixed-type in both OrthoMTA and ProRootMTA.